DEVELOPMENT OF A STRICT FEEDBACK TWO-MASS HORIZONTAL AXIS WIND TURBINE MODEL WITH EMPIRICAL POWER COEFFICIENT AND EXTERNAL STIFFNESS - Kamarudin, Muhammad Nizam; Husain, Abdul Rashid; Ahmad, Mohamad Noh; Mohamed, Zaharuddin (Journal of Advanced Manufacturing Technology (JAMT), 2015)
For a variable speed wind turbine, the control approach requires the exact dynamical model of such wind turbine to be under controlled. The established wind turbine dynamics neglect the external stiffness as an integrator to the system dynamics is introduced. In addition, many approaches assume a constant value for the coefficient, which is practically not a valid choice. Hence, this paper proposed a strict feedback model of a two-mass wind turbine system that focused on external stiffness, and also embedded empirical power coefficient in the system dynamics. The model represented in this study is a "ready-to-be-used" form that benefits the control system engineers when the feedback control approaches are taken into account.